Caring deeply about church planting twelve keys from the life of Jesus - Kao, Richard (Boca Raton, FL : Routledge, 2021)
This is a massive work. Rich Kao has prepared an education in a box for future church planters. Having planted six churches, I truly understand the dynamics behind every detail which Rich has written about. I also believe churches will take their staffs through this book to instill and inspire the apostolic passion contained in this book. This could be a game changer. Jerry Daley, Pastor and Church Planter, JerryDaley.com It's been a great honor to plant churches and do apostolic work with Rich Kao in some of the most "impossible" places. In each location Rich brought wisdom and innovation to diverse people groups. This book will help both seasoned church planters and first timers. His twelve keys are brilliant, well proven and most likely what you need to unlock your city and region to bring forth "fruit that remains." Ron Lewis, Sr. Leader, Every Nation NYC; Church planter in 20 nations I have known, respected, and served with Rich Kao for over 20 years. There is not a man I know who is more open to proactively growing in the areas of faith, flexibility, innovation, pioneering, and leadership. These traits, along with his wealth of experience, culminate in this challenging, insightful and impactful book. I would highly recommend this book not only to current church planters and church planters in training, but to anyone called to positions of leadership within Jesus' Church. Ben Goodman, Pastor of Leadership Development, Manna Church; Oversight Team, Truebridge Network Never has the need for church planting been more acute or more necessary. The world around us is beset with problems of every kind--political, social, economic, racial, and moral. The list is endless, and the difficulties are systemic and entrenched. The best minds, institutions, and efforts are being marshaled to address these problems, but are we getting to the root issues? Could it be that the solutions lie elsewhere? Indeed, the greatest reformer to ever live told us the hope we need comes from the church. Yes, the church, as anemic and as irrelevant as it may seem to some (or many). Jesus said of the community He would birth, "You are the light of the world and the salt of the earth" (Matt. 5:13-14). The church, in all its forms, from small to big, whether found in the countryside or in megacities is God's redeeming force for society, for culture, and for the nations. The church is God's secret weapon and His change agent for the world. He's all in on the church. As such the church is God's organizational servant on the earth. It's to be an enterprise of the highest quality. It's to sparkle with kingdom power, love, and truth. As Ephesians 3:10 states, "[God's] intent was that now, through the church, the manifold wisdom of God should be made known to the rulers and authorities in the heavenly realms." For such a task, outstanding leaders are needed. Great leaders are not just for the arenas of business, politics, or the military. The church must also focus on recruiting, training, and deploying the best. As the leader goes, so goes the organization. This book assists in the great endeavor of planting churches. It gives church planters a biblical and conceptual framework so they can be armed with a map for how to go about establishing new works. This framework is rooted in the humble yet glorious, small yet significant, quiet yet powerful ways of Jesus.
OCLC-licensed vendor bibliographic record.
Keywords: Jesus Christ -- Example; Kao, Richard; Church development, New; Christian leadership; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Leadership